Implementation Science and Implementation Research: A Move Forward in Improving Nursing Outcomes. - Phornphibul, Pikul; Hanucharurnkul, Somchit (Pacific Rim International Journal of Nursing Research)
In an increasingly complex and technologically advanced healthcare environment, integrating evidence-based practice and innovation is critical to improving patient outcomes. Implementation science and implementation research offer structured approaches to close the persistent gap between research evidence and routine clinical practice. This paper outlines the core concepts of implementation science and implementation research, explores their interrelationship, and reviews relevant methodological approaches. It also emphasizes the pivotal role of advanced practice nurses and policymakers in harnessing these disciplines to accelerate evidence translation and drive sustainable improvements in healthcare quality, nursing care quality, and patient outcomes.